The Relationship of Over the Counter (OTC) Facial Soap Usage and Acne Risk in Sebelas Maret University Medical Students - Jalasena Mysea, Marsyanda; Kusumawardani, Arie; Murasmita, Alamanda; Widhiati, Suci (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Acne vulgaris (AV) is a common inflammatory skin disorder among young adults. The use of over-the-counter (OTC) facial soap is a common practice for managing AV, but the impact of its frequency on acne severity remains unclear. Purpose: This study aims to determine the relationship between the frequency of OTC facial soap usage and the severity of acne vulgaris among medical students at Sebelas Maret University. Methods: This observational analytical study utilized a cross-sectional approach and involved 57 medical students at Sebelas Maret University. The questionnaire focused on the frequency of OTC face wash usage among participants. Data were analyzed using Chi-square tests and Spearman-Pearson correlation methods. Result: There is a significant relationship (p = 0.089) between the frequency of OTC face wash usage and the risk of acne vulgaris, with a weak negative correlation (r = -0.226, p = 0.092). This study set a significance level of 0.1, higher than the conventional 0.05, which limits the generalizability of the results. This decision was made to balance the accuracy of the findings with the available resource constraints. Conclusion: There’s a significant correlation between OTC facial soap usage and acne risk in Sebelas Maret University medical students, with more frequent use linked to reduced acne severity.